Correction: Assessing relative humidity dependent photoacoustics to retrieve mass accommodation coefficients of single optically trapped aerosol particles. Issue 27 (3rd July 2020) - Diveky, Matus E.; Roy, Sandra; Cremer, Johannes W.; David, Grégory; Signorell, Ruth
Abstract : Correction for 'Assessing relative humidity dependent photoacoustics to retrieve mass accommodation coefficients of single optically trapped aerosol particles' by Matus E. Diveky et al., Phys. Chem. Chem. Phys., 2019, 21, 4721–4731, DOI: ; 10.1039/C8CP06980H .